1986
DOI: 10.1021/ma00161a015
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition and melting behavior of poly(oxy-1,4-phenyleneoxy-1,4-phenylenecarbonyl-1,4-phenylene) (PEEK)

Abstract: Thermal analysis of typical poly(oxy-1,4-phenyleneoxy-1,4-phenylenecarbonyl-1,4-phenylene) (PEEK) has been carried out from 130 to 650 K for samples variously crystallized between 593 and 463 K or quenched to the glassy state. The heat capacity, Cp, is crystallinity independent to 240 K. Between 240 K and the glass transition temperature Tg (419-430 K depending on crystallization conditions) the amorphous solid has a slightly higher Cp. Above Tg poorly crystallized samples show a rigid-amorphous fraction that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
259
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(279 citation statements)
references
References 7 publications
(14 reference statements)
19
259
0
Order By: Relevance
“…This postulated model was primarily based on the observation that the magnitude and position of the low endotherm is heating rate dependent. The suitability of the model was questioned by the experimental findings that the occurrence of the high-melting endotherm precedes that of the lowtemperature endotherm, 36,38,47 which clearly contradicts the assignment of the low endotherm to the partial melting of the primary lamellae as postulated in this model.…”
Section: Introductionmentioning
confidence: 78%
“…This postulated model was primarily based on the observation that the magnitude and position of the low endotherm is heating rate dependent. The suitability of the model was questioned by the experimental findings that the occurrence of the high-melting endotherm precedes that of the lowtemperature endotherm, 36,38,47 which clearly contradicts the assignment of the low endotherm to the partial melting of the primary lamellae as postulated in this model.…”
Section: Introductionmentioning
confidence: 78%
“…The relatively narrow range of mechanical properties with respect to temperature and humidity is due to the PEEK reinforcement of the FAA-PEEK film that resists swelling and has no thermal transitions in this range. 38 The ATMPP film has a small response to temperature between 30…”
Section: Etfe-g-pvbtmamentioning
confidence: 99%
“…1(b), the low endotherm T m,1 obtained at~10 K above T c is usually attributed to an annealing effect (Cheng et al, 1986;Velikov & Marand, 1993). We also found that the low endotherm T m,1 not only shifts to a higher temperature with increase of the crystallization temperature, but also increases in magnitude with the annealing time.…”
Section: Identification Of Multiple Melting Peaksmentioning
confidence: 99%
“…The multiple melting behavior is usually explained by polydisperse lamellar thickness (dual lamellar thickness) (Cheng et al, 1986;Hsiao et al, 1993a, b), melting-recrystallization-remelting (Blundell & Osborn, 1983;Blundell, 1987) and polymorphic crystals (Sun & Woo, 1999;Ho et al, 2000;Gan et al, 2004;Ghosh et al, 2005). Both the dual lamellar thickness and melting-recrystallization-remelting can easily be confirmed by DSC measurements at different scan rates and different annealing treatments (time and/or temperature).…”
Section: Introductionmentioning
confidence: 98%